PENYULUHAN DAN KEBERDAYAAN PETANI KARET POLA SWADAYA DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Hernak Masuko Prawoto; Roza Yulida; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purposes of this research are: (1) to know the role of agricultural extension to the self-pattern rubber farming; (2) to know the empowerment rate of self-pattern rubber farmers; (3) to know how to achieve the extension goals seen from better farming, better business, and better living. This research was conducted in Logas Village and Muara Lembu Village Singingi District Kuantan Singingi Regency. The research method used survey method with 120 respondents, with details 60 farmers from Logas Village and 60 farmers from Muara Lembu Village. The results showed that the role of agricultural extension in Singingi District Kuantan Singingi Regency “not yet role” inself-pattern rubber farming activity with a score of 2,37 as seen from education, facilitation, consultation, supervision, monitoring and evaluation. The empowerment of self-pattern rubber farmersin Singingi District Kuantan Singingi Regency categorized “less powerful” with a score of 2,29 as seen from human resources, productive economy, and institutional, while the succes rate of extension goals seen from better farming, better business, and better living in Singingi District Kuantan Singingi Regency categorized “achieve enough” with a score of 2,96 Keywords: Extension Role, Empowerment, Extension Goals